In – Silico Prediction of Biological Activity Spectrum of Some Existing Local Anesthetic Drugs for Their Novel Anti-infective and Anticancer Potential - A. Bhosle , Pradnya; Karunakar, Shukla; Kshirsagar , Ajay (Journal of Neonatal Surgery, 2024)
Cancer and Infectious diseases now a day’s are becoming the major public health issue. The mutations in cancer cell and infectious agents are resulting into new variants which either is resistant or not responding to the current treatment. And discovering novel potential drugs for such new variants is time consuming, complex and laborious process that needs huge money and human efforts. Drug repurposing has attracted attention of world’s scientist as it is one of the promising fields that may give quick and cost effective solution for the treatment of such diseases that are affecting major population of the world by utilizing modern bioinformatics and computational resources. Various computational models utilized as a large source of information such as Pubchem, DrugBank, Chemspider, ChEMBL and PASS contains physicochemical and biological information on drugs. The PASS estimates the probable biological activity profiles for compounds under study based on their structural formulae presented in MOL file or SD file format. Prediction is based on the analysis of structure activity-relationships for more than 250,000 biologically active substances including drugs, drug-candidates, leads and toxic compounds. So we may use PASS for the prediction of the biological activity spectrum for existing drugs and based on the particular interest to some kind of activity and novelty of pharmacological action, we may choose which activities have to be tested experimentally. In present work the PASS studies of some already existing Local Anesthetics drugs like Benzocaine, Biphenamine, Butacaine, Cyclomethylcaine and Lidocaine were carried out on the Way2Drug portal on PASS online software version 2.0. The PASS study results obtained had revealed that amongst virtually screened Local Anaesthetic drugs Benzocaine, Biphenamine, Butacaine, Cyclomethylcaine, Lidocaine and Ambucaine have shown good Pa value ranging from 0,880 to 0,573 for Antibacterial Activity targets, 0,861 to 0,551 for Antifungal Activity targets and 0,867 to 0,593 for Anticancer Activity targets which predicts the higher probability for these drugs to be active as Antibacterial agents, Antifungal agents and Anticancer agents respectively. Amongst all virtually screened Local Anesthetic drugs Benzocaine was found to possess potent Antibacterial, Antifungal and Anticancer Activities which may be subjected for further evaluation